The Effectiveness of Master Plans: Case Studies of Biologically Active Areas in Suburban Zones - Błasik, Magdalena; Wang, Tong; Kazak, Jan (Geomatics and Environmental Engineering, 2022)
Sustainable development on a local scale requires well-functioning instruments in the spatial planning system. Any weakness in the planning system may result in forms of spatial development that are socially, environmentally or economically disadvantageous. Therefore, the aim of this study was to examine whether master plans and land development monitoring in the Polish system are effective instruments in shaping sustainable spatial development. The factor analyzed was the share of a biologically active area and four villages located near a regional city were analyzed. Data from master plans, cadaster and orthophoto maps were used in this study. Verification of land use made it possible to evaluate whether the properties meet the provisions of spatial planning documents. In each of the analyzed villages, properties that do not meet the provisions of master plans were identified. In one of the villages, more than half of the properties had a smaller share of biologically active areas than permitted by the local law. The research also analyzed alternative scenarios of the potential impact of the application of permanent vegetation on sealed surfaces. These results showed that using green roofs, for example, can significantly reduce the problem of local laws being broken. The results quantitatively confirm that the provision of master plans in the Polish system are not effective tools in regulating land development.